Serum magnesium and zinc levels in postmenopausal women depending on their menopausal status and the severity of climacteric symptoms - Grochans, Elżbieta; Karakiewicz, Beata; Brodowski, Jacek; Jurczak, Anna; Noceń, Iwona; Grzywacz, Anna; Augustyniuk, Katarzyna; Brodowska, Agnieszka (Menopause Review/Przegląd Menopauzalny, 2013)
Background : Magnesium (Mg) and zinc (Zn) may affect the incidence and severity of climacteric symptoms in postmenopausal women. Objectives : The aim of this study was to assess serum Mg and Zn levels in postmenopausal women, depending on the severity of climacteric symptoms and the time interval since the last menstrual period. Material and methods : The study included 161 postmenopausal women, who had their Mg and Zn levels determined in venous blood serum. The women were not using menopausal hormone therapy (MHT) and had their last menstrual period at least one year prior to the study. All women were healthy and did not use elimination diets. Results : The women were diagnosed as having hypomagnesaemia and hypozincaemia. The data analysis revealed statistically significant differences between Mg levels depending on the time interval since the last menstruation (p  0.05). Conclusions : 1. In postmenopausal women, not using MHT, serum Mg and Zn concentrations maintained at low levels and, what is more, the average Mg concentration decreased significantly with the time since the last menstrual period. 2. Serum Mg and Zn concentrations do not affect the severity of climacteric symptoms in postmenopausal women not using MHT.